2013
DOI: 10.21082/ijas.v11n2.2010.p65-73
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Water and Fertilizer Saving Without Compromising Rice Yield Through Integrated Crop Management

Abstract: <p>Water and fertilizer scarcity amid the increasing need of rice production challenges today’s agriculture. Integrated crop management (ICM) is a combination of water, crop, and nutrient management that optimizes the synergistic interaction of these components aiming at improving resource use efficiency, i.e. high productivity of water, land, and labor. The objectives of the study were to investigate the effects of crop establishment method, organic matter amendment, NPK management, and water management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…AWD had higher water productivity than submerged treatment due to its lower water use. This finding was also reported by [10] [26] [29] who observed that AWD resulted in higher water productivity than continuous submergence of fields. Researchers [30] reported that, continuous submergence produced optimum rice yield however, required the highest amount of water hence low water productivity.…”
Section: Effect Of Water Management On Water Use Percentage Of Watersupporting
confidence: 89%
“…AWD had higher water productivity than submerged treatment due to its lower water use. This finding was also reported by [10] [26] [29] who observed that AWD resulted in higher water productivity than continuous submergence of fields. Researchers [30] reported that, continuous submergence produced optimum rice yield however, required the highest amount of water hence low water productivity.…”
Section: Effect Of Water Management On Water Use Percentage Of Watersupporting
confidence: 89%